Aplikasi Perhitungan Pajak Pensiun Pegawai dengan PPH 21 Sebagai Variabel Moderating - Riswaya, Asep R.; Rimaya, Salma; Amijaya, Hasanah T.; Budiman, Dheni Apriantsani (Ma'soem University, 2024)
Along with the times, technology is experiencing rapid development. This advances company performance through the Tax Information System as a tool to help companies manage and process tax information more efficiently, accurately and in accordance with applicable regulations. PT Bio Farma (Persero) adalah BUMN (Badan Usaha Milik Negara) whose share ownership is fully owned by the government. PT Bio Farma (Persero) as the only producer of vaccines for humans in Indonesia. Currently there is no application that specifically helps employees calculate their pension tax easily because it is possible for errors to occur in calculating pension tax. Given these problems, to minimize errors in pension tax calculations, an application was created using the PHP framework as the programming language and MySQL as the database. The research method used in this research is the Descriptive Method. The development method used is OOAD (Object-Oriented Analysis and Design) with system design techniques using UML (Unified Modeling Language). The results showed that pension tax calculation application in PT Bio Farma (Persero) makes it easier to calculate pensions and minimizes calculation errors or delays in pension tax calculation reports.